(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In the present study we try to show, in an analytical and systematic way, the connection that exists between the destruction of employment in our economy and the closing, for legal obligation, of hundreds of thousands of small and medium companies constituted as mercantile companies, and the exigency or not of civil responsibility of the administrators of these. With such an end, we have departed from a temporary cyclical analysis of behavior of the economy, the creation and destruction of employment as well as the liquidation and shutdown of plants, apart from the casuistry on demands that demand responsibility from the social directors.